2D numerical computation for flood flow in upper river basin with tributary inflows by using water level hydrographs observed at the main stream. Issue 1 (16th January 2013) - Uchida, T.; Fukuoka, S.; Ishikawa, T.
Abstract It is difficult to clarify the characteristics of flood flows in a total river system because of insufficient data for the upper river basin. Numerical analysis is an effective tool for complementing flood observation data in space and time. The objective of this study is to develop an unsteady 2D numerical analysis method for a river with tributary inflows in the upper river basin. The inflow boundary conditions of sharp discharge hydrographs from tributaries were estimated using water level hydrographs obtained from observation stations in the main stream; these stations were installed far downstream from the confluence points. This paper demonstrates that the method could be used to investigate the propagation and transformation of the discharge hydrographs from the main and tributary streams by using the sparse water level hydrographs observed in the main stream. The installation method for the water level observation stations is also discussed.